Interaksi Hukum Islam dan Hukum Adat dalam Pembagian Warisan: Studi Kasus Masyarakat Sambori - Jariyah, Ainun; Jainuddin,; Syarif Hidayatullah, (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2025)
This study aims to analyze the understanding and practices of the Sambori community in inheritance distribution and dispute resolution, with a particular focus on the interaction between Islamic law and customary law. Using a qualitative empirical approach, data were collected through observation, in-depth interviews with religious leaders, community leaders, and village officials, as well as documentation. The findings reveal that although many members of the Sambori community are familiar with Islamic inheritance principles, they tend to adopt customary practices in distribution, as these are considered more flexible and capable of preserving family harmony. Inheritance disputes are typically resolved through family deliberation and mediation by religious or traditional leaders before resorting to the religious court. Customary law, transmitted across generations, continues to dominate the inheritance process, although there is a growing tendency, particularly among the younger generation, to adopt Islamic law. These findings highlight a dynamic interplay between religious norms and local cultural values, leading to a hybrid inheritance model within the Sambori community. It can be concluded that inheritance distribution in Sambori is not merely a legal matter but also a reflection of the community’s social, cultural, and religious values.